The role of lipids in promoting hair growth through HIF-1 signaling pathway - Jieun Seo; Kotone Matsumoto; Ayaka Nanmo; Shan Tu; Do-Won Jeong; Yang-Sook Chun; Lei Yan; Tatsuto Kageyama; Junji Fukuda (Scientific Reports)
Abstract Understanding the underlying mechanisms regulating hair regeneration is crucial, especially given the increasing demand for effective drugs to treat hair loss, which remain not fully elucidated. In the present study, we found that lipid metabolism was attenuated in the scalp tissues of patients with androgenetic alopecia. Lipid supplementation in the culture medium upregulated hair growth-related genes and promoted the proliferation of human dermal papilla cells (DPCs). By using RNA-sequencing analysis and HIF-1α knockdown in DPCs, we found that HIF-1α is a potential candidate that governs lipid-reinforced upregulation of trichogenic genes. Finally, we assessed the hair growth-promoting effects of lipids using in vitro hair follicle organoids and found that lipids accelerated the elongation of hair-shaft-like structures. Our results highlight the importance of lipids in promoting hair growth through HIF-1 signaling, suggesting that this may be a promising target for the treatment of hair loss.